PENGARUH PENYANGRAIAN TERHADAP SIFAT FISIK DAN KINERJA GASIFIKASI LIMBAH TONGKOL JAGUNG MENGGUNAKAN UPDRAFT GASIFIER - , RAUDHAH ASY SYARIFAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Corn cobs are biomass waste that contain high carbon, and are potential to be converted as gasification fuels. Previous research about corn cobs gasification using downdraft gasifier showed that corn cobs must be diminished and be drained first before being used as a gasification fuels. Roasting the corn cobs is expected to simplify the process. The objective of this research is to investigate the effect of roasting process to the physical characteristics and performance of corn cobs gasification using updraft gasifier. This research was conducted by giving different handling in roasting temperature (150, 175 and 2000C), and in roasting time (40, 50 and 60 minutes). The investigated physical parameters are water content, material density, and material rigidity. The investigated gasification performances parameters are reactor temperature, stove temperature, effective time of flame, the amount of gasification energy and waste that produced from gasification process. The result shows that roasting process can improve the physical characteristic of corn cobs as gasification fuels. The water content decreases about 5,14-10,77% (from 15,78% into 5,01-10,64%). The pressure force may be reduced about 0,643 N in roasting temperature 1500C. Roasting process also improve the corn cobs gasification performance